The effect of quotas on female representation in local politics - Monika Köppl-Turyna; Jarosław Kantorowicz (EcoAustria - Institute for Economic Research, 2020)
This work looks at the policies aimed at promoting female participation in local legislative bodies using a series of changes to electoral law in Poland. We use a difference-in-discontinuities design to examine the effect of an introduction of a female quota on female participation in local councils. We find that the female quota has a strong positive effect on the percentage of females in the local council by increasing the pool of female candidates. It does not, however, affect the individual probability of being elected as a female, suggesting that its effect on voters' preferences is limited.
Keywords: D72; B52; 330; female quota; electoral rules; female representation; regression discontinuity; difference in discontinuities